Assessing the Economic Contributions of Islamic and Conventional Banks in Asian OIC Countries - Hambali, Muhammad Soleh; Muhsyaf, Saipul Arni (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study explores the differential impacts of Islamic and conventional banks on economic growth within Asian member countries of the Organization of Islamic Cooperation (OIC). Utilizing a dataset of 1,846 observations from eight OIC countries, panel regression techniques are employed to assess the effects of these banking models on key economic growth indicators: GDP growth and GDP per capita growth. The analysis reveals that Islamic banks have a significantly greater positive impact on both GDP growth and GDP per capita growth compared to conventional banks. The findings highlight that Islamic banking principles, such as risk-sharing and asset-backed financing, contribute to a more stable and inclusive financial environment, enhancing overall economic development. The results underscore the importance of promoting Islamic banking alongside conventional banking to foster sustainable economic growth. Policymakers and financial regulators should consider incorporating the strengths of Islamic banking into regulatory frameworks to improve financial stability and resilience. Future research should investigate the long-term impacts of Islamic and conventional banking on economic growth across different regions and economic conditions, as well as the interplay between regulatory environments and financial sector performance.